2019
DOI: 10.1152/ajplung.00109.2018
|View full text |Cite
|
Sign up to set email alerts
|

Intratracheal administration of clinical-grade mesenchymal stem cell-derived extracellular vesicles reduces lung injury in a rat model of bronchopulmonary dysplasia

Abstract: Mesenchymal stem cells (MSCs) prevent the onset of bronchopulmonary dysplasia (BPD) in animal models, an effect that seems to be mediated by their secreted extracellular vesicles (EVs). The aim of this study was to compare the protective effects of intratracheally (IT) administered MSCs versus MSC-EVs in a hyperoxia-induced rat model of BPD. At birth, rats were distributed as follows: animals raised in ambient air for 2 wk ( n = 10), and animals exposed to 60% oxygen for 2 wk and treated with IT-administered p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 68 publications
2
84
0
2
Order By: Relevance
“…The composition of exosomes can be therapeutically effective, in which they give a synergistic effect when they are used as nanocarriers. It was reported that the intratracheal administration of EVs, such as exosomes that are originated from mesenchymal stem cells (MSCs), can be an effective treatment for bronchopulmonary dysplasia (BPD) in an animal model [222]. In their study, the number of alveoli in the BPD animal model was significantly increased when these EVs were administrated intratracheally.…”
Section: Nanocarriers For Cf Treatmentmentioning
confidence: 99%
“…The composition of exosomes can be therapeutically effective, in which they give a synergistic effect when they are used as nanocarriers. It was reported that the intratracheal administration of EVs, such as exosomes that are originated from mesenchymal stem cells (MSCs), can be an effective treatment for bronchopulmonary dysplasia (BPD) in an animal model [222]. In their study, the number of alveoli in the BPD animal model was significantly increased when these EVs were administrated intratracheally.…”
Section: Nanocarriers For Cf Treatmentmentioning
confidence: 99%
“…Chaubey et al demonstrated in a neonatal murine BPD model that umbilical cord MSC-derived EVs reduced pulmonary inflammation, pulmonary hypertension, and right ventricular hypertension partially mediated through the exosomal protein tumor necrosis factor alpha-stimulated gene-6 (TSG-6) [39]. In another report, umbilical cord MSC-derived EVs were as effective as the parental MSCs in protecting against hypoxia-induced lung injury in neonatal rats [40]. These beneficial effects were partially attenuated by knocking down the vascular endothelial growth factor (VEGF) gene in MSCs prior to EV isolation.…”
Section: Bronchopulmonary Dysplasiamentioning
confidence: 99%
“…Several studies have indicated that soluble factors, such as macrophage colony-stimulating factor 1, osteopontin [86], and STC1 [54], may be principally responsible for the therapeutic abilities of MSC-derived CM. MSC-derived EV [87] and exosome [73,74,88] treatments also block inflammation and reduce fibrosis and pulmonary vascular remodeling, resulting in improved lung function and the amelioration of pulmonary hypertension in hyperoxia-induced BPD. Willis et al [73] showed that MSC-derived exosomes modulated the lung macrophage phenotype by suppressing the pro-inflammatory 'M1' state and enhancing an anti-inflammatory 'M2-like' state both in vitro and in vivo.…”
Section: Msc-derived Secretomes For Bpd Therapymentioning
confidence: 99%